Understanding sex-based kinematic and kinetic differences of chasse-step in elite table tennis athletes - Yang, X.; Mei, Q.; Shao, S.; Gu,W.; He, Y.; Zhu, R.; Gu, Y. (Bioengineering, 2022)
With the progress and innovation of table tennis technology, individualized training programs may deserve special attention. This study aimed to analyze elite table tennis athletes in chasse-step, with a particular focus on sex-based biomechanical differences. A total of 36 (18 males and 18 females) elite table tennis athletes performed topspin forehand of chasse-step. Angles and moments of hip, knee, and ankle joints were calculated using OpenSim (v4.2) with marker trajectories and ground reaction forces were measured via Vicon motion capture system and AMTI in-ground force platform. Males had greater hip and knee flexion angles during the entire motion phase and greater internal rotation angles of the hip during the forward swing phase. The joint stiffness of knee in males was greater than females in the frontal plane. Females in the forward swing phase showed greater hip flexion, adduction, and internal rotation moments than males. It was suggested that the difference may be due to the limitation of anatomical structures in sexes. Male table tennis athletes should strengthen lower extremity muscle groups to improve performance, while female table tennis athletes should focus on hip joint groups to avoid injury. The sex differences presented in this study could help coaches and athletes to develop individualized training programs for table tennis.